Synthesis and characterization of wound healing hydrogel using keratin protein from chicken feathers - Mohamed Saad, Bala Husain (2022)
Poultry industries produce a large amount of feather waste, which harm the environment and human health. On the other hand, chicken feathers primarily contain keratin protein, which can be exploited to produce products for biomedical applications. In the present research, keratin was extracted from chicken feathers and was applied to prepare the hydrogel films for wound healing applications. Some biopolymers were used to prepare two different hydrogel films, such as polyvinyl alcohol (PVA) and polyvinylpyrrolidone (PVP) and corn starch, using the freeze-thawing technique at temperature -20°C. All biopolymers used in this study are inexpensive, non-toxic, and have been successfully applied in various biomedical applications. The first formulation, namely KS-hydrogels were prepared using keratin, polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP) and corn-starch. The second formulation, namely K-hydrogels were prepared using keratin, polyvinyl alcohol (PVA), and polyvinylpyrrolidone (PVP). The effect of keratin in hydrogel films for both samples was examined by Fourier-transform infrared spectroscopy (FTIR), confirmed the presence of keratin, scanning electron microscope (SEM) examined surface morphology, and thermogravimetric analysis (TGA) showed thermal stability was affected with different concentrations of keratin protein. The porosity of the hydrogel decreased for KS-70 and K-70 hydrogels at 33.57% and 45.22%, respectively, due to their relatively high interconnecting and low porous structure due to their low water content with high keratin content. The swelling ratio of KS70 and K70 hydrogels and 30.66% and 31.58 % after 1440 min due to its relatively increased crosslinking density with high keratin content. On the other hand, tensile strength (stress vs strain) has seen improvement with the increase of the keratin protein content into hydrogel films. Furthermore, it was found that K-hydrogel films were better than KS-hydrogel films because K-hydrogel films provided an appropriate hardness for using potential wound healing applications. Moreover, keratin release increased with increasing keratin content; the highest release was 95.72% in K70 after 96 hr on the KS-hydrogel films and K-hydrogel films release was 81% in K70 after 96 hr Higuchi square root model best predicted the keratin release behaviour. The Higuchi square root was the optimal model of keratin kinetics release for all the hydrogel films. The optimal conditions for hydrogel film synthesis were determined using response surface methodology (RSM) with four selected parameters, including (A, 30-70 v/v %), PVA/PVP ratio (B, 30-70 v/v %), freeze and thawing (C, 3-7 cycles), and mixing temperature (D, 50-70 °C). The model determined that the optimal conditions for the best formation were 50% keratin content, 50% PVA/PVP, five freeze-thaw cycles, and a mixing temperature of 60°C. ANOVA demonstrated the model is significant and has a p-value less than 0.05, with the R2 was 97.3. In vivo model on the rabbits indicated that keratin-based hydrogel film could accelerate wound healing compared with other groups after 19 days. Dependence on the results obtained in this study, the keratin hydrogel film was successfully prepared for potential wound healing applications.